EFISIENSI PEMBIAYAAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI JAWA TIMUR PERIODE 2014-2017. ANALISIS DENGAN METODE DEA (CRS,VRS, dan Skala) - Aziza Hanifa Khairunnisa; Nisful Laila (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
This research aimed to find out the efficiency level of financing of Islamic Rural Bak in East Java. Input variables used were the rights of third party on profit sharing and PPAP cost, while output variable used was main operational income. Method used to measure efficiency level was Data Envelopment Analysis (DEA) with the assumption of Variable Return to Scale and the input and output orientations. The measurement of efficiency value with VRS assumption resulted three efficiency values, which are Technical Efficiency (VRS), Economic Efficiency (CRS), and Scale Efficiency. Then, these three values were analyzed further to get to know the source of inefficiency of financing in inefficient Islamic Rural Bank. Keywords: BPRS, Data Envelopment Analysis (DEA)Efficiency, Financing